Intergenic regions of Borrelia plasmids contain phylogenetically conserved RNA secondary structure motifs - Delihas, Nicholas (BioMed Central, 2009)
BACKGROUND: Borrelia species are unusual in that they contain a large number of linear and circular plasmids. Many of these plasmids have long intergenic regions. These regions have many fragmented genes, repeated sequences and appear to be in a state of flux, but they may serve as reservoirs for evolutionary change and/or maintain stable motifs such as small RNA genes. RESULTS: In an in silico study, intergenic regions of Borrelia plasmids were scanned for phylogenetically conserved stem loop structures that may represent functional units at the RNA level. Five repeat sequences were found that could fold into stable RNA-type stem loop structures, three of which are closely linked to protein genes, one of which is a member of the Borrelia lipoprotein_1 super family genes and another is the complement regulator-acquiring surface protein_1 (CRASP-1) family. Modeled secondary structures of repeat sequences display numerous base-pair compensatory changes in stem regions, including C-G→A-U transversions when orthologous sequences are compared. Base-pair compensatory changes constitute strong evidence for phylogenetic conservation of secondary structure. CONCLUSION: Intergenic regions of Borrelia species carry evolutionarily stable RNA secondary structure motifs. Of major interest is that some motifs are associated with protein genes that show large sequence variability. The cell may conserve these RNA motifs whereas allow a large flux in amino acid sequence, possibly to create new virulence factors but with associated RNA motifs intact.